Instructional Leadership of Private and Public Schools in Kosovo - Krasniqi Rina; Shabani Arafat; Bajrami Demush (SEEU Review, 2022)
Managing a company or organization in today’s market is a challenge that each leader has to face. Companies have to adapt and embrace challenges, or they will be left behind by the competitors in the market. The leadership of a company has to be creative in order to fulfill the needs of the customers, the market, and its employees.